2021
DOI: 10.1093/ptj/pzab075
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Telerehabilitation in Physical Therapist Practice: An Umbrella and Mapping Review With Meta–Meta-Analysis

Abstract: Objective Telerehabilitation is an option that should be adapted as soon as possible in order to face the crisis caused by COVID-19. An umbrella and mapping review with meta–meta-analysis (MMA) of the available scientific evidence was performed to determine if telerehabilitation could be an effective alternative to conventional rehabilitation in physical therapist practice. Methods A systematic review of reviews and a synthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
94
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(100 citation statements)
references
References 45 publications
4
94
1
1
Order By: Relevance
“…Furthermore, those studies have found conflicting results for this variable. Further studies are required to evaluate the cost-effectiveness of this rehabilitation model, the barriers encountered by patients when performing TR, and the patients' acceptance of the model [21]. According to studies, numerous factors can help TR to develop at a slower pace and require further time to be able to convince the patient of its effectiveness as conventional approaches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, those studies have found conflicting results for this variable. Further studies are required to evaluate the cost-effectiveness of this rehabilitation model, the barriers encountered by patients when performing TR, and the patients' acceptance of the model [21]. According to studies, numerous factors can help TR to develop at a slower pace and require further time to be able to convince the patient of its effectiveness as conventional approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these barriers, TR could be a better treatment option for some patients. Furthermore, it has considerable advantages, although further study is required to investigate its effectiveness in other conditions [21,22]. With the development of technology, and in some conditions that individuals with a disability cannot travel for face-to-face interventions, for example in the COVID-19 pandemic, the need for TR has increased and simultaneously has sped up the adop-tion of digital culture, worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…12 Telerehabilitation provides a viable alternative that could be superior to no rehabilitation and as effective as conventional rehabilitation. 13 14 We investigated possible superiority of a telerehabilitation programme for COVID-19 (TERECO) over no rehabilitation with regard to functional exercise capacity, lower limb muscle strength…”
Section: Introductionmentioning
confidence: 99%
“…Telerehabilitation was an invaluable tool in providing continuity of care during very risky and uncertain times. Although it has been an emerging technological innovation in the field of rehabilitation for some years, 7 the absolute need for telerehabilitation presented itself during this public health crisis. 8 This was the first time we implemented institution-wide telerehabilitation, and we did so at a rapid pace, for a large number of patients and clinicians.…”
Section: Expert Opinionmentioning
confidence: 99%